Pengembangan Lagu “Ayo Gosok Gigi” untuk Meningkatkan Keterampilan Menggosok Gigi pada Anak Usia Dini - Yunefi, Rendi; Primalasari, Septian (NHM PRESS, 2023)
Dental and oral health problems in young children as a vulnerable group can disrupt their growth and development. Efforts that can be made are brushing your teeth properly every day. However, if you haven't brushed your teeth properly, it can cause problems with your teeth. The aim of this research is to develop learning media through songs to improve teeth brushing skills in young children. The type of research is Research and Development (R&D), with stages namely determining potential and problems; collecting data; designing products; product development; product validation includes internal testing by three experts, namely music experts, material experts and media experts; product revision; user test; product revision; and product manufacturing. Assessment results from internal expert validation tests from three experts, namely music experts, media experts and material experts. The results of the music expert's validation test showed that the feasibility score was 84% in the very appropriate category (without revision) with the suggestion to consider adding a child's voice to the song's vocals. The results of the media expert validation test showed that the feasibility score was 100% in the very feasible category (without revision) with the suggestion that the song could be heard for the first time in the care services laboratory. The results of the material expert validation test showed that the feasibility score was 100% in the very feasible category (without revision) with the suggestion to mention fluoride toothpaste in the song lyrics. The song “Ayo Gosok Gigi” was perfected and tested in the field for user testing. User testing on 20 students at the Pembina 2 State Kindergarten in Jambi City and it was found that the feasibility score was 88% in the very feasible category (without revision). The song